Determinasi Tingkat Penyaluran Kredit Pemilikan Rumah (Periode Setelah Kebijakan Loan to Value) - Dwianingrum, Titia (Jurnal Ilmiah Mahasiswa FEB, 2014)
This research aims to find out how the impact of loan to value policy on bank value in determining the amount  of mortgage  loans which are distributed,  as well as  knowing what is  the dominant variable affecting the bank in determining the amount of the mortgage loan portfolio. In addition, during the  years  2010  -  2014  the number of  mortgage  loans  which are  distributed  increased continuously  and  decreased  since  2013.  The method used  in  this  research  is to use  panel data regression  which is a combination  of  the data  time series  and  cross section.  Sample of this research choosen by purposive sampling technique. This study resulted that after the loan to value policy, only DPK and LDR variable are  significant affected mortgage  lending and have positive coefficient, while  the variable CAR, NPLs, ROA, BOPO, and BI rate has no significant effect on mortgage lending.Keywords: Mortgage Lending, Loan to Value, DPK, CAR, NPLs, ROA, LDR, BOPO, BI Rate